NuRadioReco: a reconstruction framework for radio neutrino detectors - Glaser, Christian; Nelles, Anna; Plaisier, Ilse; Welling, Christoph; Barwick, Steven W.; Garcia-Fernandez, Daniel; Gaswint, Geoffrey; Lahmann, Robert; Persichilli, Christopher (European Physical Journal C: Particles and Fields, 2019)
While the radio detection of cosmic rays has advanced to a standard method in astroparticle physics, the radio detection of neutrinos is just about to start its full bloom. The successes of pilot-arrays have to be accompanied by the development of modern and flexible software tools to ensure rapid progress in reconstruction algorithms and data processing. We present NuRadioReco as such a modern Python-based data analysis tool. It includes a suitable data-structure, a database-implementation of a time-dependent detector, modern browser-based data visualization tools, and fully separated analysis modules. We describe the framework and examples, as well as new reconstruction algorithms to obtain the full three-dimensional electric field from distributed antennas which is needed for high-precision energy reconstruction of particle showers.
CRIS-Team Scopus Importer:2019-06-18